2015
DOI: 10.1002/pbc.25790
|View full text |Cite
|
Sign up to set email alerts
|

Imaging Patterns and Outcome of Posterior Reversible Encephalopathy Syndrome During Childhood Cancer Treatment

Abstract: Background Diagnosis of posterior reversible encephalopathy syndrome (PRES) requires presence of headache, seizures, impaired vision, or altered mentation accompanied by specific imaging findings. We aimed to study long-term clinical and radiologic outcome of PRES in children with cancer to augment limited available data. Procedure Retrospective review of children with cancer who were diagnosed with PRES. Results We identified PRES in 21 males and 16 females amongst the 5,217 children treated during the st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

10
46
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 54 publications
(57 citation statements)
references
References 13 publications
10
46
1
Order By: Relevance
“…The present study showed that PRES was a common neurotoxicity during early ALL treatment with the NOPHO ALL2008 protocol, in line with previously reported data . Older age, T‐cell leukemia, CNS involvement at diagnosis, and high‐risk block treatment were significant risk factors for PRES.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…The present study showed that PRES was a common neurotoxicity during early ALL treatment with the NOPHO ALL2008 protocol, in line with previously reported data . Older age, T‐cell leukemia, CNS involvement at diagnosis, and high‐risk block treatment were significant risk factors for PRES.…”
Section: Discussionsupporting
confidence: 92%
“…Posterior reversible encephalopathy syndrome (PRES), first described in 1996, has been reported in children with acute lymphoblastic leukemia (ALL), usually occurring during the three first months of therapy . The reported incidence of PRES in pediatric ALL varies from 1.6% to 4.5% .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…With early recognition and treatment of CNI‐induced neurotoxicity, including PRES, the majority of patients will have no remaining neurological symptoms . However, life‐threatening complications may occur and acquired neurological damage may persist . In the three MMA patients with PRES some remaining clinical abnormalities were found (case 1) …”
Section: Discussionmentioning
confidence: 99%
“…28 However, life-threatening complications may occur 32 and acquired neurological damage may persist. 33,34 In the three MMA patients with PRES some remaining clinical abnormalities were found (case 1). 11,24 4.2 | FGF-21 and CNI-induced neurotoxicity, including PRES, in transplanted MMA patients…”
Section: Outcomementioning
confidence: 97%